Квазіперіодичні розв'язки лінійних вироджених систем звичайних диференціальних рівнянь другого порядку - Єрьоменко, В.О.; Алілуйко, А.М. (Український математичний журнал, 2010)
Установлены достаточные условия существования квазипериодического решения системы обыкновенных дифференциальных уравнений второго порядка с вырожденной симметрической матрицей при производных второго порядка для произвольной квазипериодической неоднородности. We establish sufficient conditions for the existence of quasiperiodic solutions of a system of ordinary second-order differential equations with degenerate symmetric matrix of the second derivatives for an arbitrary quasiperiodic inhomogeneity.